Power of Indian traditional foods and their benefits - Sireesha , G (Journal of Postharvest Technology, 2024)
This review research paper aims to comprehensively examine the nutritional and health benefits of  traditional Indian foods, shedding light on their potential to promote well-being and address  contemporary health challenges. Drawing upon the principles of nutrition, ethnobotany, and traditional  knowledge systems, this paper establishes a theoretical framework that underscores the significance  of Indian traditional foods in maintaining health and preventing diseases. It explores the synergy  between traditional food wisdom and modern nutrition science. A systematic literature review  methodology was employed to collect and analyze data from a wide range of sources, including  scientific journals, ethnobotanical texts, and nutritional databases. The selected studies covered  various aspects of Indian traditional foods, including ingredients, preparation methods, and their impact  on health. The findings of this research reveal that Indian traditional foods encompass a diverse array  of ingredients, preparation techniques, and regional variations that collectively provide a balanced and  nutritionally rich diet. These foods are often rich in essential nutrients, antioxidants, and bioactive  compounds, which are associated with numerous health benefits, including improved digestion,  enhanced immunity, and reduced risk of chronic diseases such as diabetes and heart disease. This  review highlights the potential of Indian traditional foods as a valuable resource for promoting public  health and nutrition. Understanding and incorporating these foods into modern diets can have practical  implications for addressing contemporary health challenges. Additionally, this research underscores  the importance of preserving and promoting traditional food knowledge, which is essential for  maintaining cultural diversity and sustainable food systems. This research contributes to the existing  © The Author(s) This is an Open Access  article licensed under a  Creative Commons license:  Attribution 4.0 International  body of knowledge by providing a comprehensive synthesis of the nutritional and health benefits of  traditional Indian foods. It bridges the gap between traditional wisdom and modern science,  emphasizing the importance of preserving and integrating traditional dietary practices in a rapidly  changing world.
Keywords: Indian traditional foods; health benefits; ethnobotany; sustainable food systems.